(3YQhV CfOdSjs - (3GdNRQLj, CHh eMeO, VjGA GdOjf, YHO Gddg Hf eMeO, (B626 (3g`s
(3ChdgG (B:s
(3bGd GdabjQhHYO abO bUOJ aj gPG GdeNJUQ Cf CPcQ Ydd GdCYGQjV GdCQHY hGdKdGKjf hGdVQhH GdKdGKI hGdSJjf NGUI hdG CJYQV dTjA ef RMGa GdMTh ZGdHG hVYJ ajg SJI hYTQjf HjJGs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3JbGQHJ EPG TeQhG (B*** (3Edi Xdge Chi , GdeJOGQc CUdg aGYdf KeGf eQGJ , OGQc Gdbhe JWaF ZQGe EP OQjO Gdghi HGdeYfi LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 124s
(3eYLe GdeDdajf(B: 1 / 460s
(3cTa GdXfhf(B: 2 / 1135s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdYQhV hGdbhGajs